Molecular Tools for Typing Mycoplasma pneumoniae and Mycoplasma genitalium - Dumke, Roger (Frontiers in Microbiology, 2022)
Mycoplasma pneumoniae and Mycoplasma genitalium are cell wall-less bacteria with strongly reduced genome content and close phylogenetic relatedness. In humans, the only known natural host, the microorganisms colonize the respiratory or genitourinary mucosa and may cause a broad range of clinical presentations. Besides fundamental differences in their tissue specificity, transmission route and ability to cause prevalence peaks, both species share similarities such as the occurrence of asymptomatic carriers, preferred populations for infection and problems with high rates of antimicrobial resistance. To further understand the epidemiology of these practically challenging bacteria, typing of strains is necessary. Since the cultivation of both pathogens is difficult and not performed outside of specialized laboratories, molecular typing methods with adequate discriminatory power, stability and reproducibility have been developed. These include the characterization of genes containing repetitive sequences, of variable genome regions without the presence of repetitive sequences, determination of single and multi-locus variable-number tandem repeats and detection of single nucleotide polymorphisms in different genes, respectively. The current repertoire of procedures allows reliable differentiation of strains circulating in different populations and in different time periods as well as comparison of strains occurring subsequently in individual patients. In this review, the methods for typing M. pneumoniae and M. genitalium, including the results of their application in different studies, are summarized and current knowledge regarding the association of typing data with the clinical characteristics of infections is presented.